Addressing the second victim phenomenon in Israeli health care institutions - Rinat Cohen; Yael Sela; Rachel Nissanholtz-Gannot (BMC, 2023)
Abstract Background The 'second victim' phenomenon (SVP) refers to practitioners who experience a negative physical or emotional response, as well as a professional decline, after participating or witnessing an adverse event. Despite the Israeli Ministry of Health's implementation of specific protocols regarding the overall management of adverse events in health organizations over the past decade, there is limited knowledge regarding healthcare managers' perceptions of the 'second victim' occurrence. Methods A phenomenological qualitative approach was used to identify an accurate view of policy. Fifteen senior risk manager/and policy makers were interviewed about their knowledge and perceptions of the 'second victim'. Topics addressed included reporting mechanisms of an adverse event, the degree of organizational awareness of 'second victim', and identifying components of possible intervention programs and challenges to implementing those programs. Results Examining current procedures reveals that there is limited knowledge about uniform guidance for health care organizations on how to identify, treat, or prevent SVP among providers. The employee support programs that were offered were sporadic in nature and depended on the initiative of a direct manager or the risk manager. Conclusions Currently, there is little information or organizational discussion about the possible negative effects of AE on healthcare practitioners. To provide overall medical care that is safe and effective for patients, the health system must also provide a suitable response to the needs of the medical provider. This could be achieved by establishing a national policy for all healthcare organizations to follow, raising awareness of the possible occurrence of SVP, and creating a standard for the subsequent identification, treatment and future prevention for providers who may be suffering.